Transient overexpression of adh8a increases allyl alcohol toxicity in zebrafish embryos. - Nils Klüver; Julia Ortmann; Heidrun Paschke; Patrick Renner; Axel P Ritter; Stefan Scholz (PLoS ONE)
Fish embryos are widely used as an alternative model to study toxicity in vertebrates. Due to their complexity, embryos are believed to more resemble an adult organism than in vitro cellular models. However, concerns have been raised with respect to the embryo's metabolic capacity. We recently identified allyl alcohol, an industrial chemical, to be several orders of magnitude less toxic to zebrafish embryo than to adult zebrafish (embryo LC50 = 478 mg/L vs. fish LC50 = 0.28 mg/L). Reports on mammals have indicated that allyl alcohol requires activation by alcohol dehydrogenases (Adh) to form the highly reactive and toxic metabolite acrolein, which shows similar toxicity in zebrafish embryos and adults. To identify if a limited metabolic capacity of embryos indeed can explain the low allyl alcohol sensitivity of zebrafish embryos, we compared the mRNA expression levels of Adh isoenzymes (adh5, adh8a, adh8b and adhfe1) during embryo development to that in adult fish. The greatest difference between embryo and adult fish was found for adh8a and adh8b expression. Therefore, we hypothesized that these genes might be required for allyl alcohol activation. Microinjection of adh8a, but not adh8b mRNA led to a significant increase of allyl alcohol toxicity in embryos similar to levels reported for adults (LC50 = 0.42 mg/L in adh8a mRNA-injected embryos). Furthermore, GC/MS analysis of adh8a-injected embryos indicated a significant decline of internal allyl alcohol concentrations from 0.23-58 ng/embryo to levels below the limit of detection (< 4.6 µg/L). Injection of neither adh8b nor gfp mRNA had an impact on internal allyl alcohol levels supporting that the increased allyl alcohol toxicity was mediated by an increase in its metabolization. These results underline the necessity to critically consider metabolic activation in the zebrafish embryo. As demonstrated here, mRNA injection is one useful approach to study the role of candidate enzymes involved in metabolization.